2007
DOI: 10.1177/0748233708089039
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of chelators and antioxidants on mancozeb-induced toxicity in rat hippocampal astrocytes

Abstract: Mancozeb, manganese ethylene-bis-dithiocarbamate with zinc salts, is one of the most commonly used fungicides in the United States. Epidemiological and experimental data showed that mancozeb causes detrimental effects on various organ systems including the reproductive, endocrine, immune, and central nervous system. Increasing evidence has shown a strong association between pesticides and neurodegenerative diseases. In this study, we examined the neurotoxic potential of mancozeb in rat hippocampal astrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Phase-contrast microscopy of treated cells showed distortion of cell shape, a decreased cell number, cytoplasmic vacuolization, floating cells, and cellular debris when compared with the controls. These observations were similar in appearance as presented in a study with another dithiocarbamate, Mancozeb (Tsang and Trombetta, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Phase-contrast microscopy of treated cells showed distortion of cell shape, a decreased cell number, cytoplasmic vacuolization, floating cells, and cellular debris when compared with the controls. These observations were similar in appearance as presented in a study with another dithiocarbamate, Mancozeb (Tsang and Trombetta, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Mancozeb exposure was strongly associated with increased incidence of thyroid disease in pesticide applicators (Trivedi et al, 1993;Goldner et al, 2010). Reports are available on the toxicity of mancozeb on liver and kidney (Ksheerasagar and Kiliwal, 2003), on central nervous system (Nordby et al, 2005;Tsang and Trombetta, 2007). Histological studies of the testis of the mice treated with high doses of mancozeb revealed spermatogenesis inhibition (Ksheerasagar and Kaliwal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They found that significant cells death was caused by 250 and 500 μM MnCl 2 exposure for 24 h. However, Yin et al [21] found that the peaking of MTT reduction and LDH leakage occurred between Mn exposure for 2 h and 6 h that was different with our exposure time period. In addition, mancozeb, manganese ethylene-bis-dithiocarbamate with zinc salts, was observed to cause cytotoxicity on the cultured astrocytes [22]. It was also shown that exposure to Mn at a concentration of either 500 μM or 1 mM Mn elicited a dose-dependent increase in the LDH release of the N9 microglial cells [23].…”
Section: Discussionmentioning
confidence: 95%